Effect of Leadership and Work Discipline to Employee Performance through the Job Satisfaction as Intervening Variable in National Civil Service Agency Regional Office X Denpasar - Wayan Arya Paramarta; Ni Made Gunstri; Ni Ketut Laswitarni; I Gede Januana Tegmini (Privietlab, 2021)
The purpose of this study was to determine the performance of employees at the National Civil Service Agency Regional Office X Denpasar which is influenced by leadership and work discipline through job satisfaction. The population in this study was employees in executive positions within the National Civil Service Agency Regional Office X Denpasar. The number of samples used in this study was 56 as determined by purposive sampling. The results from this research shows that leadership has a positive and significant effect on job satisfaction, work discipline has a positive and significant effect on job satisfaction, leadership has no significant effect on performance, work discipline has a positive and significant effect on performance, job satisfaction has a positive and significant effect on employee performance, the indirect effect of leadership on performance through job satisfaction has a positive but not significant effect, the indirect effect of work discipline on performance through employee job satisfaction at National Civil Service Agency Regional Office X Denpasar has a positive and significant effect.